Supporting Written Scientific Explanations of Middle-School Students with Learning Disabilities - Brooke A Moore; Steve J Skoczek; Hannah W Wince (The Advocate, 2024)
Students with learning disabilities deserve high-quality science instruction that supports them in constructing scientific explanations as a means toward building their science content knowledge. We examined written scientific explanations of 66 middle-school students with learning disabilities from rural Kansas school districts, comparing them with a matched set of 66 peers without learning disabilities within the same classrooms following instruction using a Next Generation Science Standards (NGSS) aligned curriculum that embedded explicitly taught supports for writing scientific explanations. Students were assessed at pre- and post-unit on overall content learning and change in written scientific explanations. Post-unit written explanations of students with learning disabilities were statistically significantly better following instruction but overall content knowledge gains were only practically significant. Differences between post-unit written explanations of students with learning disabilities compared to their peers without learning disabilities were not statistically significantly different, yet students without learning disabilities did show statistically significant growth in overall content knowledge.
Keywords: content instruction; science instruction; learning disabilities; general education